2009
DOI: 10.1111/j.1600-0528.2009.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an oral health literacy instrument for adults

Abstract: Initial testing of OHLI suggested that it is a valid and reliable instrument to evaluate oral health literacy among adults, although additional work is needed to investigate the instrument's predictive validity and sensitivity to change using oral health outcomes with population groups known to be at high risk of low functional oral health literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
188
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(232 citation statements)
references
References 23 publications
27
188
1
6
Order By: Relevance
“…In the testing of TS-REALD, 19 % were found to have low oral health literacy [23], while the corresponding figure for OHLI was only 3 % [29]. However, the authors of OHLI state that their study population were young and well educated adults who were frequent users of dental care, which may explain the low percentage of people with lower health literacy levels.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In the testing of TS-REALD, 19 % were found to have low oral health literacy [23], while the corresponding figure for OHLI was only 3 % [29]. However, the authors of OHLI state that their study population were young and well educated adults who were frequent users of dental care, which may explain the low percentage of people with lower health literacy levels.…”
Section: Discussionmentioning
confidence: 68%
“…The significant bivariate correlations were confirmed in multiple regression analyses. In the initial testing of the oral health literacy instrument OHLI [29], significant associations between health literacy scores and health knowledge scores were reported. In the health literacy research, many studies have demonstrated a relationship between health knowledge and health literacy [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other studies had used different instrument to assess OHL and also reported the relationship between OHL and other factors (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Mean (Sd)mentioning
confidence: 99%
“…14 Uncertainty about CWF may reflect levels of health literacy or the ability of individuals to obtain, understand and act upon health information and to make appropriate decisions. 22 A direct association between caregiver health literacy and knowledge has been previously reported. 23 In addition, it has recently been suggested that oral health literacy is a fundamental dimension that confers oral health impacts beyond education and socio-demographic characteristics.…”
Section: Oral Healthmentioning
confidence: 99%